Immunolocalization of NLRP3 Inflammasome in Normal Murine Airway Epithelium and Changes following Induction of Ovalbumin-Induced Airway Inflammation. (18th March 2012) - Tran, Hai B.; Lewis, Martin D.; Tan, Lor Wai; Lester, Susan E.; Baker, Leonie M.; Ng, Jia; Hamilton-Bruce, Monica A.; Hill, Catherine L.; Koblar, Simon A.; Rischmueller, Maureen; Ruffin, Richard E.; Wormald, Peter J.; et al.
Abstract : Little is known about innate immunity and components of inflammasomes in airway epithelium. This study evaluated immunohistological evidence for NLRP3 inflammasomes in normal and inflamed murine (Balb/c) airway epithelium in a model of ovalbumin (OVA) induced allergic airway inflammation. The airway epithelium of control mice exhibited strong cytoplasmic staining for total caspase-1, ASC, and NLRP3, whereas the OVA mice exhibited strong staining for active caspase-1, with redistribution of caspase-1, IL-1 β and IL-18, indicating possible activation of the NLRP3 inflammasome. Active caspase-1, NLRP3, and other inflammasome components were also detected in tissue eosinophils from OVA mice, and may potentially contribute to IL-1 β and IL-18 production. In whole lung, inRNA expression of NAIP and procaspase-1 was increased in OVA mice, whereas NLRP3, IL-1 β and IL-18 decreased. Some OVA-treated mice also had significantly elevated and tightly correlated serum levels of IL-1 β and TNF α . In cultured normal human bronchial epithelial cells, LPS priming resulted in a significant increase in NLRP3 and II-lp protein expression. This study is the first to demonstrate NLRP3 inflammasome components in normal airway epithelium and changes with inflammation. We propose activation and/or luminal release of the inflammasome is a feature of allergic airway inflammation which may contribute to disease pathogenesis.